Heteroatom Doping Synergistic Iron Nitride Induced Charge Redistribution of Carbon based Electrocatalyst with Boosted Oxygen Reduction Reaction - Dr. Yuyu Guo; Dr. Dianyu Xu; Dr. Shuting Li; Dr. Jinxi Han; Prof. Qi Yang; Prof. Zhengqiang Xia; Prof. Gang Xie; Prof. Sanping Chen; Prof. Shengli Gao (ChemElectroChem, 2023)
Abstract Oxygen reduction reaction (ORR) is Achilles’ heel of zinc‐air battery. The ideal electrocatalyst for ORR should combine both high activity and high stability. In order to achieve this goal, a new N, S co‐doped carbon coated Fe3N nanoparticles electrocatalyst with redistributed charge was designed and synthesized. The doping of S elements destroyed the ordered structure of carbon matrix, which cooperated with Fe3N nanoparticles to cause charge redistribution of carbon atoms. Furthermore, the carbon shell protected Fe3N from corrosion during the electrocatalytic process. Fe3N/NSC electrocatalyst showed excellent ORR property with E1/2=0.86 V, and the zinc‐air battery assembled based on it could run stably for more than 650 hours. This work provides a strategy to regulate the redistributed charge of carbon atoms to boost its electrocatalytic activity and stability together.